Слаще любых обещаний: роман / Пенни Джордан - Джордан Пенни (Любовный роман, 2001)
Экземпляры: ф. 14 (20140321) / Инвентарный номер: 41679 / Цена: 10.00 / Авт.знак: Д 42 / ГРНТИ: 17.82 / ББК: 84(4Вел)-44